2017
DOI: 10.1016/j.jes.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance of low temperature Microbial Fuel Cells (MFCs) catalyzed by mixed bacterial consortia

Abstract: Microbial Fuel Cells (MFCs) are a promising technology for treating wastewater in a sustainable manner. In potential applications, low temperatures substantially reduce MFC performance. To better understand the effect of temperature and particularly how bioanodes respond to changes in temperature, we investigated the current generation of mixed-culture and pure-culture MFCs at two low temperatures, 10°C and 5°C. The results implied that the mixed-culture MFC sustainably performed better than the pure-culture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Phylogenetic analysis showed that electricigens in these MFCs always consisted of the strains discussed above. For instance, Tkach et al identified 59 strains in the mixed bacterial consortia of an MFC while Geobacter and Pseudomonas were the dominant genera [91]. The microbial communities are dynamically changed during the MFC operation processes and their dynamics can be also analyzed using similar strategies.…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…Phylogenetic analysis showed that electricigens in these MFCs always consisted of the strains discussed above. For instance, Tkach et al identified 59 strains in the mixed bacterial consortia of an MFC while Geobacter and Pseudomonas were the dominant genera [91]. The microbial communities are dynamically changed during the MFC operation processes and their dynamics can be also analyzed using similar strategies.…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…and Pseudomonas sp. formed on the anode surface by mixed cultures using activated sludge in acetate‐fed MFC 15,20,21 . Furthermore, benzene, toluene, and phenol degradation by Geobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial biolms are sensitive to temperature to optimize their growth and electrocatalytic activity. 148,149 Depending on the temperature range in which they grow, bacteria can be divided into three groups, psychrophiles (<15 C), mesophiles (15-40 C), and thermophiles (>40 C). Most of the MFC designs have been performed in mesophilic ranges, 147,150,151 which suggest that most of the electroactive bacteria are functioning in mesophilic temperatures.…”
Section: Operation Conditionmentioning
confidence: 99%